PROBLEMATIKA PENDIDIKAN ANAK DALAM KELUARGA DI MASA PANDEMI COVID-19 - Nur Syamsiyah; Andri Hardiyana (Jurnal Harkat : Media Komunikasi Gender, 2021)
Abstract. This study aims to identify and describe the problems of children's education in families during the COVID-19 pandemic, especially on the problem of the concept of learning from home (BDR) in Cirebon regency. This research was conducted in the Cirebon regency by taking a random sample of 10 with a total of 57 families as respondents. The time of the research was carried out in August-October 2020 using a qualitative descriptive method. Data collection techniques are observation techniques, as well as documentation studies, and filling out questionnaires via Google form. The data are analyzed using techniques that are data reduction, data presentation, scoring, data analysis, and inference. The results of this study implement 3 family functions, namely 1) religious functions: guiding, controlling the implementation of prayer, reciting the Qur'an, praying before and after studying, and before and after eating 2) The function of affection. This function is shown by the seriousness of parents in assisting BDR. 91% of mothers accompany BDR children, while 9% of mothers do not assist for reasons of work. On the other hand, there’s 62% of fathers accompanying BDR, and 38% of fathers did not assist BDR because the mentoring process had been completed in the afternoon by the mother. And 3) the function of socialization and education in the implementation of BDR encountered the following problems: a. Children do not understand the subject mater, b. Too many tasks make children feel bored, c. the child is not serious and does not concentrate when studying at home, d. children do not like or feel uncomfortable when studying with their parents. Abstrak. Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan problematika pendidikan anak dalam keluarga pada masa pandemi covid 19 terutama pada permasalahan konsep Belajar dari Rumah (BDR) di Kabupaten Cirebon.  Penelitian ini dilaksanakan di Kabupaten Cirebon dengan mengambil sampel secara acak di  10 dengan jumlah responden sebanyak 57 keluarga. Adapun waktu pelaksanaan penelitian dilakukan pada Agustus-Oktober 2020 dengan menggunakan metode deskriptif kualitatif. Teknik pengumpulan data yang adalah teknik observasi, studi dokumentasi, dan pengisian angket melalui google form. Teknik analisis data yang digunakan adalah reduksi data, penyajian data, penskoran, analisis data, dan penyimpulan. Hasil penelitian ini mengimplementasikan 3 fungsi keluarga yaitu 1) fungsi keagamaan: membimbing, mengontrol pelaksanaan sholat, mengaji, berdoa sebelum dan sesudah belajar, dan sebelum dan sesudah makan, 2) Fungsi kasih sayang. Fungsi ini ditunjukkan dengan keseriusan orang tua dalam mendampingi BDR. Ibu mendampingi anak BDR sebanyak 91% sementara itu 9% ibu tidak melakukan pendampingan dengan alasan bekerja. Disisi lain, Ayah juga melalukan  62% dalam mendampingi BDR, dan 38% ayah tidak melakukan pendampingan BDR dengan alasan karena proses pendampingan sudah selesai dilakukan di siang hari oleh ibunya, 3) Fungsi sosialisasi dan pendidikan dalam pelaksanaan BDR mengalamai kendala: a. materi tidak terlalu dipahami, b. Rasa jenuh dengan tugas yang banyak, c. anak tidak serius dan tidak konsentrasi saat belajar di rumah, d. anak tidak suka atau merasa tidak nyaman ketika belajar dengan orang tuanya.